Behavioral competencies in higher education : a conceptual framework. - Ali, Mass Hareeza
The purpose of this study was to develop a behavioral competency framework for academic staff in the context of higher education in Malaysia. Literature review revealed a gap in the relationship between emotional intelligence (EI), academics behavioral competencies and performance efficiency in the context of teaching and learning in higher education. The development of a conceptual framework is based on the integration of theoretical models and various, including coaches and efficiency of teaching, instructional system design (ISO) using ADDIE model, training delivery competencies (IBSTPI) and adult learning. This paper specifies propositions to explain the relationship between constructs based on the previous research gap. In theory, this study will contribute to the development of academic competence behavior, before, during and after teaching in the classroom or training delivery. In practice, this framework will generate information to assist public and private higher education in the process of selection, performance management and development.